Lao Biodiversity : A Priority for Resilient Green Growth - World Bank (World Bank, Washington, DC, 2020)
The Lao PDR sits at the intersection of four critical ecoregions and is home to some of the world’s biologically richest and most endangered terrestrial and aquatic ecosystems and species. The biodiversity endowment is crucial to the Lao economy, as the goods and ecosystem services it provides are essential to reduce poverty, secure livelihoods, and drive a greener economic growth model. But Lao biodiversity is in danger. The highest priority threats to the country’s biodiversity values include climate change, illegal logging, the illegal wildlife trade, infrastructure development in and around protected areas, and expansion of agriculture and settlements. This World Bank report outlines key challenges and priority actions to ameliorate the main threats to biodiversity and to sustainably utilize the biodiversity assets to help drive Lao PDR’s green economy.